Reread a History: Another Narration from the Biography of Aga Mohammad Khan Qajar A Critique on the Book "Iran's History in the Qajar Period: The Aga Mohammad Khan Era" - Alireza Mollaiy Tavany (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2020)
This article criticizes Gholam Hossein Zargarinejad’s book that named "History of Iran in the Qajar Period: The Age of Aga Mohammad Khan”. The life and work of Aga Mohammad Khan Qajar is one of the controversial topics in the Iranian history. There has been much research and historical novels written about him so far. Generally, bloody, cruel, and vengeful figures have been drawn in both the Pahlavi and Islamic Republic-era historiography discourse and independent research. That would have been a different fate for Iran if it had not abolished Zandieh’s government. Zargirinejad is one of the scholars who echoed this view in his earlier works but in his book “History of Iran in the Qajar Period: The Age of Aga Mohammad Khan”. He has attempted to alter this picture with a critical reading of sources and documents and to draw completely different figures. A person who is not only rumors about his cruelty, especially the blindness of the people of Kerman or the Caucasus, but also the opposite, was the only one among the claimants of power, including Lotfali Khan Zand, who completely thought about Iran and the revival of its historical realm. This article attempts to critically evaluate the views and views of Zargarinejad.